Sex-specific impacts of caffeine on body composition: commentary on a retrospective cohort study - Anna Vittoria Mattioli (Journal of the International Society of Sports Nutrition)
Background: Understanding the impact of caffeine intake on body composition is a topic of growing research interest. The article “Association Between Caffeine Intake and Fat-Free Mass Index: A Retrospective Cohort Study” by Tian et al. explored this relationship, highlighting a positive correlation between caffeine consumption and fat-free mass index (FFMI). In this letter to the editor, we discuss the broader implications of these findings, emphasizing the need for further exploration of the underlying biological and lifestyle factors influencing caffeine’s effects.Objective: To provide critical insights into the mechanisms and contextual factors that may explain the observed association between caffeine intake and FFMI, with particular focus on sex-specific differences, hormonal influences, and lifestyle interactions.Methods: This letter to editor builds on the findings of Tian et al., drawing from related literature and prior research to contextualize the potential mechanisms and broader implications of caffeine’s impact on body composition. The discussion highlights key areas requiring further investigation, including the role of hormonal modulation, genetic variability, and long-term effects on muscle health.Discussion: The positive association between caffeine intake and FFMI, particularly among women and younger populations, underscores the ergogenic potential of caffeine in enhancing muscle performance and metabolic efficiency. This letter expands on the study by emphasizing the role of hormonal factors, such as estrogen’s modulation of CYP1A2, the liver enzyme critical for caffeine metabolism. The discussion also highlights the complex interplay between caffeine and other lifestyle factors. Finally, this commentary calls attention to the need for more research into the differential effects of caffeine sources, such as energy drinks and supplements, which often include additional ingredients with distinct metabolic and cardiovascular effects. These alternative sources may influence body composition differently than traditional coffee-based caffeine intake, an area that remains underexplored.